1994
DOI: 10.1172/jci116970
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of multiple maternal genotypes of human immunodeficiency virus type I in infants infected by vertical transmission.

Abstract: The extent of nucleotide variation within the HIV-1 env hypervariable domains serves as a marker of virus genotypes within infected individuals and as a means to track transmission of the virus between individuals. We analyzed env VI and V2 sequences in longitudinal samples from two HIV-1-infected mothers, each with three children infected by maternal transmission of the virus. Sequences in samples that were obtained from two infants at 2 d and 4 wk after birth displayed more variation in V1 and V2 than matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 59 publications
5
46
1
Order By: Relevance
“…Sequencing additional regions in the biological clones from these motherchild pairs may show whether the minor variant in the child either has evolved from the major HIV-1 variant in the child or was transmitted simultaneously. Transmission of multiple HIV-1 variants via the vertical route has previously been suggested (33) and may be related to the long exposure time in utero or to the large inoculum to which the newborn may be exposed during delivery. (41).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing additional regions in the biological clones from these motherchild pairs may show whether the minor variant in the child either has evolved from the major HIV-1 variant in the child or was transmitted simultaneously. Transmission of multiple HIV-1 variants via the vertical route has previously been suggested (33) and may be related to the long exposure time in utero or to the large inoculum to which the newborn may be exposed during delivery. (41).…”
Section: Discussionmentioning
confidence: 99%
“…He and others have used such data to suggest the presence of selective pressure in determining which HIV-1 variants are transmitted (1). Data from other studies however, have shown a more random pattern of transmission of multiple and/or major maternal HIV-1 variants (22,25). The lack of consensus among these studies may be due to the facts that each study compared only a few mother-infant pairs and the results were not correlated with the timing of transmission.…”
mentioning
confidence: 96%
“…A recent study indicates that an interindividual variability in HIV co-receptor expression can be observed for trophoblastic cells from early placentas, indicating a possible mechanism for HIV variant selection (Mognetti et al 2000). However, many variants (Essajee et al 1996), intrasubtype recombinants (Kampinga et al 1997) and even genotypes (Lamers et al 1994, Janini et al 1998) may be transmitted from the mother to the offspring. No difference in preferential transmission of one genotype above others has been detected (Contag et al 1997, Campodonico et al 1998.…”
Section: Hiv-1 Type and Selective Transmissionmentioning
confidence: 99%
“…No difference in preferential transmission of one genotype above others has been detected (Contag et al 1997, Campodonico et al 1998. Some studies found no difference between viral isolates from mother and infant, indicating that selection does not occur in all cases (Lamers et al 1994). A case of one HIV-1 infected mother transmitting a selected variant to one child and multiple variants to another has been described (Wade et al 1998), indicating that, if selection occurs, it might be circumstancial or dependent on a variety of factors, of which high numbers of different variants in high concentrations could be one.…”
Section: Hiv-1 Type and Selective Transmissionmentioning
confidence: 99%